2020
DOI: 10.1038/s41467-020-17791-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of the active Gs-coupled human secretin receptor

Abstract: The class B secretin GPCR (SecR) has broad physiological effects, with target potential for treatment of metabolic and cardiovascular disease. Molecular understanding of SecR binding and activation is important for its therapeutic exploitation. We combined cryo-electron microscopy, molecular dynamics, and biochemical cross-linking to determine a 2.3 Å structure, and interrogate dynamics, of secretin bound to the SecR:Gs complex. SecR exhibited a unique organization of its extracellular domain (ECD) relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 72 publications
7
66
0
Order By: Relevance
“…Similar to most peptide agonists present in active class B1 GPCR complex structures (Zhao et al 2019, Dong et al 2020, Qiao et al 2020, both semaglutide and taspoglutide adopted a continuous helix with their C-terminus bound to the ECD and N-terminus inserted deeply into the TM core (Figures 1 and S4). The N terminus of GLP-1, particularly residues at position 7, 8, 9, 10, 12, 13 and 15, as well as several residues at the C terminus are crucial for GLP-1 binding and/or activity (Adelhorst et al 1994).…”
Section: Peptide Binding To Glp-1rmentioning
confidence: 82%
See 2 more Smart Citations
“…Similar to most peptide agonists present in active class B1 GPCR complex structures (Zhao et al 2019, Dong et al 2020, Qiao et al 2020, both semaglutide and taspoglutide adopted a continuous helix with their C-terminus bound to the ECD and N-terminus inserted deeply into the TM core (Figures 1 and S4). The N terminus of GLP-1, particularly residues at position 7, 8, 9, 10, 12, 13 and 15, as well as several residues at the C terminus are crucial for GLP-1 binding and/or activity (Adelhorst et al 1994).…”
Section: Peptide Binding To Glp-1rmentioning
confidence: 82%
“…As described above, the static consensus structures for taspoglutide, semaglutide and GLP-1 bound, active GLP-1Rs are remarkably similar. For other class B1 GPCRs, we have demonstrated that the active complexes are dynamic and that dynamics can contribute to the pharmacological behaviour of bound ligands (Dong et al 2020. To understand and visualize the dynamic motions in GLP-1R complexes, 3D variability analysis implemented in cryoSPARC was performed.…”
Section: D Variability Analysis Reveals Distinct Dynamic Motions In mentioning
confidence: 99%
See 1 more Smart Citation
“…This was confirmed in the 3D variance analysis of the conformational dynamics of the complex comparing principal components of motion for complexes with and without Nb35, with the greatest difference observed for the relative motion between the G and G interface. Our application of 3D variance analysis to recently solved structures of class B GPCRs, including adenomedullin-1 (AM1) and AM2 receptors 19 , the secretin receptor 20 and GLP-1R bound to peptide and small molecule agonists 14 has revealed common rocking and rotational motions of the G protein relative to the receptors. This is consistent with transient formation and breakage of interactions that are likely to be important in receptor-mediated G protein recruitment and activation, and low resolution for parts of ICL3 and the extension of H8 for class B GPCRs 3,8,9,15,[19][20][21][22][23][24][25][26][27][28] are consistent with transient interactions between these domains and the G protein.…”
Section: Discussionmentioning
confidence: 99%
“…A key conformational change required nucleotide exchange is outward movement of the AHD of Gs, relative to the ras-like domain. The AHD of Gαs in the nucleotide-free state is highly mobile, thereby occupying different positions around the ras-like domain 30 , and it is poorly resolved in most consensus cryo-EM maps of solved class B GPCR-G protein complexes 3,8,9,15,[19][20][21][22][23][24][25][26][27][28] . When bound with Nb35, 3D multivariate analysis of PF 06882961-GLP-1R-DNGs complex revealed translational motion between open ("up" position) and more closed ("down" position) conformations of the AHD.…”
Section: Discussionmentioning
confidence: 99%